Molecular Engineering for Function‐Tailored Interface Modifier in High‐Performance Perovskite Solar Cells. Issue 27 (30th May 2022) - Sung, Sae Jin; Im, Jino; Kim, Geunjin; Moon, Chan Su; Yoo, Jason J.; Shin, Seong Sik; Jeon, Nam Joong; Ma, Boo Soo; Kim, Dong Jun; Kim, Taek‐Soo; Seo, Jangwon
Abstract: Interface modification of perovskite solar cells (PSCs) has been widely explored not only to achieve defect passivation but also to facilitate charge transport and stabilize the physical/electrical contact at device interfaces. In this study, [2‐(9 H ‐carbazol‐9‐yl)ethyl]phosphonic acid (CEPA) is introduced as an interface modifier at the interface of perovskite and the hole transporting material (HTM) layer into n‐i‐p PSCs. CEPA reduces surface traps, manipulates the surface dipole for energy‐level alignment, and induces molecular interaction at the interface of the CEPA‐HTM for enhanced interfacial adhesion energy and good mechanical stability. The power conversion efficiency of interface‐optimized PSC is 23.6% using a 2D/3D perovskite structure, representing the highest efficiency among poly(triarylamine) HTM‐based devices. The encapsulated CEPA‐treated PSCs maintain nearly 90% of their initial efficiency during a damp heat lasting for more than 1530 h and retain their initial efficiency during continuous operation under illumination. Abstract : An interface modifier (IM) that interacts not only with perovskite but also with hole transporting material is introduced for efficient and stable perovskite solar cells. The best solar cell employing rational IM exhibits a power conversion efficiency of 23.6% with a 2D/3D perovskite structure. Thermal and operational stabilities of interface‐optimized devices are demonstrated.